Water productivity at basin level: Methods, benefits, and shortcomings - Vosti, S.A.; Torres, M. (CGIAR Challenge Program on Water and Food, 2006)
This research program is part of the CGIAR Challenge Program on Water & Food and is supported by the International Water Management Institute, the Brazilian Enterprise for Agricultural Research (Embrapa), and the Department of Land, Air and Water Resources, the Department of Agricultural and Resource Economics, and the Center for Natural Resources Policy Analysis, all at the University of California, Davis. The views expressed in this research brief need not reflect those of the sponsors.